WOMEN EMPOWERMENT AND ECONOMIC CONTRIBUTION: STATISTICAL ANALYSIS WITH THE CHI-SQUARE TEST - Kaur, Navneet (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This study investigates the relationship between women’s labor force participation and a country’s economic classification using statistical analysis. By employing a Chi-Square Test of Independence on a publicly available dataset of global labor force participation rates, this research evaluates whether income level categories (Low, Lower-Middle, Upper-Middle, High) significantly affect women’s engagement in the labor force. The findings suggest a strong association between income group and participation rate category, underscoring the need for policy interventions tailored to economic contexts.